Mechanical response of CH 3 NH 3 PbI 3 nanowires - Ćirić, L. (2019)
We report a systematic study of the mechanical response of methylammonium lead triiodide CH3NH3PbI3 nanowires by employing bending measurements using atomic force microscope on suspended wires over photo-lithographically patterned channels. Force-deflection curves measured at room temperature give a Young's modulus between 2 and 14 GPa. This broad range of values is attributed to the variations in the microcrystalline texture of halide perovskite nanowires. The mechanical response of a highly crystalline nanowire is linear with force and has a brittle character. The braking modulus of 48 ± 20 MPa corresponds to 100 μm of radius of curvature of the nanowires, rendering them much better structures for flexible devices than spin coated films. The measured moduli decrease rapidly if the NW is exposed to water vapor.